Digital transformation in e-commerce logistics: a case study on the digital maturity of the last-mile area - Tabim, Verônica Maurer (2024)
Highlights: This article addresses the diagnosis of digital maturity in e-commerce logistics, specifically the final delivery stage, known as the last-mile. The last-mile has greater digitization demand than traditional logistics due to the extreme speed of the virtual world during shopping, where customers transfer these same expectations to delivery services. Goal: The main objective of this work is to evaluate the digital maturity of the last-mile area of operation of an e-commerce logistics company. Methodology: This study evaluates the maturity model in a case study with the company E-commerceCo. Interviews were conducted with key employees for data gathering. Results: The proposed method allows defining and analyzing the digital maturity of the last-mile area of the company in question, understanding strengths, such as a culture open to innovation and digitally mature, and weaknesses, such as technical limitations imposed by the main system used and lack of cybersecurity barriers. Limitations of the investigation: Since it is a single case study, it does not allow a broad generalization to industries in other branches. Another limitation is that this study is focused on Brazilian logistics operations, which may differ from other countries. Practical implications: This research is relevant to serve as a reference for other companies in the e-commerce logistics sector to assess their digital maturity from the proposed model and compare common challenges and opportunities. In addition, it will help the studied company to create a successful digital transformation strategy. Originality / Value: We propose a new approach on how to evaluate the digital maturity of the last-mile area of operation of an e-commerce logistics company.